2022
DOI: 10.3847/1538-4357/ac4160
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neutral Hydrogen in Setting the Abundances of Molecular Species in the Milky Way’s Diffuse Interstellar Medium. II. Comparison between Observations and Theoretical Models

Abstract: We compare observations of H i from the Very Large Array (VLA) and the Arecibo Observatory and observations of HCO+ from the Atacama Large Millimeter/submillimeter Array (ALMA) and the Northern Extended Millimeter Array (NOEMA) in the diffuse (A V ≲ 1) interstellar medium (ISM) to predictions from a photodissociation region (PDR) chemical model and multiphase ISM simulations. Using a coarse grid of PDR models, we estimate the density, FUV radiation fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…5. SiO is detected in the two directions observed here where Rybarczyk et al (2022a) showed that UVdominated, equilibrium chemical models were unable to account for the high HCO + column densities. These are also the directions where shells are observed.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…5. SiO is detected in the two directions observed here where Rybarczyk et al (2022a) showed that UVdominated, equilibrium chemical models were unable to account for the high HCO + column densities. These are also the directions where shells are observed.…”
Section: Discussionmentioning
confidence: 71%
“…Six of the eight features with SiO detected have N (HCO + ) 10 12 cm −2 , which is the column density at which Rybarczyk et al (2022a) showed that equilibrium chemical models fail to explain the observed column densities of several molecular species, including HCO + . In particular, Rybarczyk et al (2022a) argued that non-equilibrium effects (i.e., shocks) are necessary to explain the HCO + column densities and H I temperatures for features in the direction of 3C111A and BL Lac, where indeed we detect SiO, and where there appears to be an association with dynamical processes (shell expansion from a previous generation of star formation). Meanwhile, only one of the structures with N (HCO + ) > 10 12 cm −2 has no detected SiO 2 .…”
Section: High Sio Abundances In the Diffuse Ismmentioning
confidence: 95%
See 3 more Smart Citations